(untitled) (Desarrollo, Estado y Espacio, 2022)
The premise of this article is that although the central role of the State in developing economies is indispensable, decentralisation of decision-making authority is inevitable in the governance of territorially large societies such as the People’s Republic of China (PRC). A key component in the developmental experience of the PRC, as regards the two distinct models of development—Maoist and Dengist—has been a marked decentralisation of power and authority, an inevitable requirement in a territorially large and diverse country like China. The crucial point, however, is that during the Maoist and the Dengist eras, the strategies of development were distinguished by, among other features, two very distinct types of decentralisation.Whereas the Maoist developmental strategy was predominantly administrative, the Dengist strategy of decentralisation is predominantly market-driven. Besides, it is highly imperative to note that there are a great many points of departure between the Maoist and the Dengist developmental strategies. This article briefly traces the origins of decentralisation in post-1949 China and compares the Maoist and Dengist policies with regard to decentralisation. It essentially focuses on decentralisation strategies in the period of market reforms and the significance of the Chinese model of development for the developing countries.